The fiber in the diet of Iberian pigs and ability to limit growth - Paniagua Breña M.; Izquierdo Cebrián M.; Ayuso Carrizosa D.; Hernández-Matamoros A.; González Sánchez E. (7th International Symposium on the Mediterranean Pig, 2012)
In order to limit the growth of Iberian pigs during the rearing period, is to consider to include in the diet fibrous material, to reduce food intake under ad libitum feeding and thus energy. Incorporation levels are 300, 450 and 600 g kg, using as fiber source, sugar beet pulp (as soluble fiber) and cereal straw (as -1insoluble fiber). A total of 20 pure Iberian pigs was used (into 5 groups of 4 pigs each). The pigs started the experiment with 84 kg of live weight and remains in the experiment for 4 weeks, to reach a live weight of 102 kg. Growth and feed intake was controlled and average daily gain and feed conversion was determined. The ad libitum intake of 300 to 600 g kg of fiber -1produces a decrease in all the productive parameters except in feed conversion. The effect of the type of fiber over the feed intake was significant with B-coefficients of -0.039 for SBP and -0.052 for CS. The cereal straw has a major effect in the decrease of the intake than the sugar beet pulp.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)